Privacy in Social Networks: An Analysis of Facebook - Külcü, Özgür; Henkoğlu, Türkay (Information World, 2014)
The only way to beware of the risks and threads of Facebook, the most commonly used social networking site in the world and Turkey, is to be a conscious user changing the default settings or simply not to have a Facebook account. In Turkey, there is still not any study in which personal information shared though social networking sites has been evaluated in terms of privacy in the literature. For this reason, the findings obtained as a result of this study have a great importance in the sense of displaying the general picture of the current situation and drawing attention to the risks of the issue in Turkey where there are not legal arrangements efficiently protecting the users. This study aims to investigate the Facebook privacy of information professionals who are members of KUTUP-L, and to determine the sensitivity and level of awareness of the information professionals in Turkey. Facebook user profiles of 400 information professionals each of whom are KUTUP-L members have been analyzed in the study considering 32 different privacy settings. A privacy score has been calculated for each user, and the relations between all privacy results have been analyzed. The findings at the end of the study show that information professionals in Turkey pay attention to privacy, and most of the users change the default settings in order to protect their personal information.
Keywords: Social networks; Facebook; Personal and sensitive data; Privacy